Antimicrobial stewardship program activities in India: an appraisal - Chauhan, Janki; Chakraverty, Raja; Pathan, Saman (International Journal of Basic & Clinical Pharmacology, 2022)
Human antimicrobial misuse/overuse/irrational use is one of the main drivers of antimicrobial resistance (AMR) and in the presence of a rapidly drying up antibiotic pipeline, it becomes imperative that we learn to use antibiotics judiciously and responsibly. In 2010, India was adjudicated to be the world’s largest consumer of antibiotics and hence curbing injudicious use of antibiotics is a must. Antibiotic abuse happens due to common fallacies such as a belief that broad spectrum antibiotics are “safer” and failure to distinguish between bacterial infections and non-bacterial infections and non-infectious syndromes. In addition, antibiotics for durations longer than necessary, redundant cover (like double gram negative or double anaerobic cover) or treatment of colonizers or contaminants also constitute inappropriate antibiotic use. A stewardship program implementing rational antibiotic use is mandatory to curb irrational antibiotic use. Antimicrobial stewardship is defined as a set of coordinated interventions designed to measure and improve the appropriate use of antibiotics by promoting the selection of the optimal choice, dose, duration and route of the antibiotic which in turn lead to improved patient outcomes and decreased adverse effects.